2021
DOI: 10.3390/s21248207
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping Vulnerability and Countermeasure in Infrared Communication for IoT Devices

Abstract: Infrared (IR) communication is one of the wireless communication methods mainly used to manipulate consumer electronics devices. Traditional IR devices support only simple operations such as changing TV channels. These days, consumer electronic devices such as smart TV are connected to the internet with the introduction of IoT. Thus, the user’s sensitive information such as credit card number and/or personal information could be entered with the IR remote. This situation raises a new problem. Since TV and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In Akgul's work in 2011 [12], authors proposed a new protocol and applied the Tiny Encryption Algorithm (TEA) symmetric cipher algorithm [13], but the reason for suggesting the new protocol and using the encryption algorithm was not sufficient. More recently, Kim and Suh focused on the structure of the IR transaction data packet and indicated that the packet can be divided into two sections: address and command (data) [14]. The authors applied secret key encryption for the IR data and suggested that rather than encrypting the entire message, partial encryption of only address section can be beneficial to save power and hardware area.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Akgul's work in 2011 [12], authors proposed a new protocol and applied the Tiny Encryption Algorithm (TEA) symmetric cipher algorithm [13], but the reason for suggesting the new protocol and using the encryption algorithm was not sufficient. More recently, Kim and Suh focused on the structure of the IR transaction data packet and indicated that the packet can be divided into two sections: address and command (data) [14]. The authors applied secret key encryption for the IR data and suggested that rather than encrypting the entire message, partial encryption of only address section can be beneficial to save power and hardware area.…”
Section: Related Studiesmentioning
confidence: 99%
“…We have adopted the idea of partially encrypting plain messages from [14], instead of encrypting the entire message, to save circuit area and reduce data transmission time. Additionally, we have adopted the non-linear S-box table pair (forward and inverse) proposed in Section 3.4.…”
Section: Self-reconfiguring Pseudo Random Address Generatormentioning
confidence: 99%
“…PVD has a cyclic redundancy check (CRC) to check for errors [36], but it can only confirm that data corruption has occurred. Therefore, we benchmarked the method used by the IR remote system [37,38] to reliably send this message. This message consists of a simple binary system ('yes' or 'no') encapsulated within 1 byte; however, to ensure accuracy, an additional byte for data verification (inverted data) is included, doubling its size to 2 bytes.…”
Section: Probe Vehicle Data (Pvd)mentioning
confidence: 99%
“…Also, there are types of routing attacks [15]. Passive attack-A type of attack in which the intruder accesses the communication link and listens to the private communication channel, e.g., eavesdropping [16]. Man-in-the-middle attack-This attack takes place when the external attacker breaches communication between two trusted entities and steals critical data [17].…”
Section: Network Layermentioning
confidence: 99%